AKRONIM, BLENDING, DAN KLIPING BAHASA GENERASI Z DI TIKTOK: KAJIAN MORFOLOGI - Shafira Fitria Putri; Muhammad Rinzat Iriyansah; Agus Iryana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of social media has influenced people's communication patterns, especially Generation Z. One platform that has played a role in the formation of new language variations is TikTok. This research aims to describe the forms of acronyms, blending, and clipping used by Generation Z on TikTok, explain their linguistic characteristics, identify the factors behind their emergence, and examine their implications for the use of Indonesian in the future. This research uses a descriptive qualitative method with a morphological approach. Research data is in the form of words, terms and expressions that contain acronyms, blending and clipping processes in TikTok content and user interactions. Data collection techniques are carried out through listening, note-taking and documentation techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The research results showed that there were 39 data consisting of 24 acronyms, 7 blending, and 8 clipping. Acronyms are the most dominant form used because they are able to support fast and efficient communication. The use of blending and clipping shows Generation Z's linguistic creativity in creating new forms of language that suit digital communication needs. Research findings show that Indonesian is dynamic and adaptive to technological developments. However, excessive use of slang has the potential to blur the boundaries between formal and informal language use, so adequate linguistic literacy is required.